« Dessinez votre vie en 6-8 cases ». La bande dessinée expertisée par la justice des enfants (1945-1960) - Véronique Blanchard; Mathias Gardet (Comicalités, 2023)
From 1945 onwards, the French Ministry of Justice set up observation centers for minors brought before juvenile courts. Several observation methods were devised, led by psychologists using classic tests (Binet-Simon, Rorschach, TAT, etc.) as well as newer protocols (free writing or drawing). A recurrent exercise in both boys’ and girls’ observation centers was the prompt to draw one’s life in the form of a comic strip in several panels. The youth did not understand that they were being tested. These life stories, condensed into a few panels, are powerful revelations of everyday life and accounts of the trajectories of young people grappling with post-war French society. Despite the fact that historians have been reluctant to handle these archives until now, we believe that their analysis opens up new avenues of research. While absolutely avoiding any psychologizing interpretation, we aim to show that these comics give a voice to teenagers who tell their stories in a different way.